9 - Announcement: Justinian F. RWEYEMAMU Memorial Award - Journal systeme (Africa Development, 1983)
The Council for the Development of Economic and Social Research in Africa (CODESRIA), the Dag Hammarskjôld Foundation, the Inter national Foundation for Development Alternatives (IFDA) and the Third World Forum (TWF) announce the Justinian F. RWEYEMAMU Memorial Award for 1985. Justinian F. RWEYEMAMU (1942—1982), scholar and practi tioner of development, was professor of economics at the University of Dar-es-Salaam, Dean of its Faculty of Social Sciences, Permanent Secretary in the Ministry of Planning and Personal Assistant to President Julius K. NYERERE. Internationally recognized, he was sucessively a member of the United Nations Committee for Development Planning and of the Secretariat of the Brandt Commission and worked for the last two years of his life in the office of the United Nations Director General for Develop ment and International Economic Cooperation. His books include: — Underdevelopment and Industrialization in Tanzania, a Study of perverse capitalist development, Socialist planning in Tanzania, and Industrializa tion and income distribution. He contributed many articles to Africa Development, the Journal of Modern African Studies, Development Dia logue and other periodicals. He was also the Chairman of CODESRIA and member of the Executive Committee of IFDA and the TWF. With a view to perpetuating his memory and encouraging African students to follow his example, the four international institutions with which he was closely associated have established a Justinian F. RWEYEMA MU Memorial Fund to which a number of his friends and colleagues have already made donations. The Award will be financed by the interests accruing to the Fund. The Award will be attributed to an African post-graduate student or a researcher for a significant contribution to enlarging the endogenous knowledge base needed for Africa's local and national development. Deve lopment will be understood in a broad sense, that is encompassing its cultural, political, social, technological as well as economic dimensions. Papers should be based on personal research and may consist of general or case studies contributing empirically and/or theoretically to development studies. The Award is intended to enable the winner to continue his/her research on a comparative basis in an African society other than her/his own.· Students presenting papers should be willing and prepared to travel to another African country to continue their work on a comparative basis. Papers may be written in Arabic, English, French and Portuguese. They must not exceed 100 clearly typed pages of approximately 250 words each.Three copies must reach the Executive Secretary of CODESRIA (Po. Box 3304, Dakar, Senegal) by 30 November 1984 at the latest. Papers will be submitted to a jury chaired by Ismail-Sabri ABDALLA, Chairman, Third World Forum, including Claude AKE, Dean Faculty of Social Sciences, University of Port-Harcourt, Nigeria; Simon MBILINYI, Permanent Secretary in Salam, Tanzania; Marie-Angélique SAVANE, President of Association of African Women for Research and Development; Teresinha LOPES, Organizacao da Mulher Angolana, as well as Abdallah BUJRA, Executive Secretary of CODESRIA, who will act as the Secretary of CODESRIA. The Award will consist of an airticket and a stipend facilitating the winner to travel to and spend 2/3 months in an African University or research centre. The paper receiving the Award will be published by CODESRIA. The first (1985) Justinian F. RWEYEMAMU Award will be presented to the winner on the occasion of the CODESRIA Conference scheduled to take place in Addis Ababa in the Spring of 1985.